COMPARATIVE CHARACTERISTICS OF MORPHOLOGICAL INDICES OF THE STOMACH IN EXPERIMENTAL LIVER DAMAGE - Sanoyev Farhod Fayzulloyevich, (TADQIQOTLAR, 2025)
Annotation:  Numerous  fundamental  studies  devoted  to  the  problem  of  the complex  influence  of  exogenous  and  endogenous  effects  on  the  human  body  have proven their depressive effect on the body's regulatory systems. At the same time, the study of morphological indices of gastric tissue, sensitive to homeostasis disturbances in experimental conditions with liver damage, remains relevant for researchers.